SCHOOL MANAGEMENT IN THE IMPLEMENTATION OF THE NATIONAL ASSESSMENT PROGRAM AT DARUL ABRAR PRIVATE SMP SCHOOL - Nurma Elysa (Media Inovasi Pendidikan dan Publikasi, 2024)
To realize the mandate in Law no. 20 of 2003 concerning the National Education System, the government always carries out reforms that are adapted to the needs of the times. Before the National Assessment, the student evaluation system from a cognitive perspective was known as the National Examination. The implementation of the national exam using the UNKP system is considered to have several technical shortcomings, namely